The correct spelling of the nomen of the lost shark Carcharhinus obsolerus White, Kyne & Harris, 2019 (Chondrichthyes, Carcharhinidae) - White, William T.; Kyne, Peter M.; Harris, Mark (Zootaxa, 2019)
White et al. (2019) described a new species of whaler shark represented by only three specimens from South-east Asia, all collected prior to 1934. They proposed the nomen Carcharhinus obsolerus with the justification of: “The specific name is Latin for ‘extinct’ (obsolerus) in allusion to the fact that the species has not been recorded in many decades.” Dubois & Séret (2019) stated that the epithet obsolerus was “doubtless” an incorrect spelling which must be corrected to obsoletus. However, the Dubois & Séret (2019) publication becomes confusing in its discussion around the wording of the related Articles in the International Code of Zoological Nomenclature (32.2, 33.2 and 32.5) and lacks a clear conclusion.